The impact of international organizations on the environment: An empirical analysis - Axel Dreher; Magdalena Ramada-Sarasola (ETH Zurich, KOF Swiss Economic Institute, 2006)
When analyzing the impact of international organizations on the environment, two main issues arise. First, we have to quantify the participation of the organizations on countries they deal with. Second, the environmental impact of this involvement has to be measured. This paper attempts to do this. We employ panel data to empirically analyze whether and to what extent the presence of IMF, World Bank, regional Multilateral Development Banks, WTO and Global Environmental Facilities has an impact on environmental governance and outcomes. Our results for a large number of countries and years show that the international organizations affect the environment directly via their impact on CO2 emissions. Projects financed by World Bank, ADB, UNDP, and membership in the WTO increase emissions, while IADB projects reduce emissions. EBRD and UNEP do not significantly affect CO2 emissions, while the AfDB increases emissions after 1985 only. Taking the indirect impact through trade liberalization into account, however, the WTO reduces emissions, while the IADB increases emissions. There is some evidence that the international organizations investigated here also influence SO2 emissions, water pollution, and round wood production; environmental governance is not affected.
Keywords: Q53; Q56; F34; F35; 330; International Organizations; Environment; Governance; IMF; World Bank; WTO; Trade Liberalization; Internationale Organisation; Internationale Wirtschaftsorganisation; Mitgliedschaft; Außenhandelsliberalisierung; Kohlendioxid; Umweltbelastung; Umweltpolitik; Schätzung